Peroxisomal Metabolite and Cofactor Transport in Humans - Chornyi, Serhii; IJlst, Lodewijk; van Roermund, Carlo W. T.; Wanders, Ronald J. A.; Waterham, Hans R. (Frontiers in Cell and Developmental Biology, 2021)
Peroxisomes are membrane-bound organelles involved in many metabolic pathways and essential for human health. They harbor a large number of enzymes involved in the different pathways, thus requiring transport of substrates, products and cofactors involved across the peroxisomal membrane. Although much progress has been made in understanding the permeability properties of peroxisomes, there are still important gaps in our knowledge about the peroxisomal transport of metabolites and cofactors. In this review, we discuss the different modes of transport of metabolites and essential cofactors, including CoA, NAD+, NADP+, FAD, FMN, ATP, heme, pyridoxal phosphate, and thiamine pyrophosphate across the peroxisomal membrane. This transport can be mediated by non-selective pore-forming proteins, selective transport proteins, membrane contact sites between organelles, and co-import of cofactors with proteins. We also discuss modes of transport mediated by shuttle systems described for NAD+/NADH and NADP+/NADPH. We mainly focus on current knowledge on human peroxisomal metabolite and cofactor transport, but also include knowledge from studies in plants, yeast, fruit fly, zebrafish, and mice, which has been exemplary in understanding peroxisomal transport mechanisms in general.